4(b+3)=9

Simple and best practice solution for 4(b+3)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(b+3)=9 equation:


Simplifying
4(b + 3) = 9

Reorder the terms:
4(3 + b) = 9
(3 * 4 + b * 4) = 9
(12 + 4b) = 9

Solving
12 + 4b = 9

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + 4b = 9 + -12

Combine like terms: 12 + -12 = 0
0 + 4b = 9 + -12
4b = 9 + -12

Combine like terms: 9 + -12 = -3
4b = -3

Divide each side by '4'.
b = -0.75

Simplifying
b = -0.75

See similar equations:

| 12x+11=156 | | 28y+4x=4 | | -3p/2;0 | | x^2=16y-32 | | 25=18-2y | | -2(5x-9)+7=-10X+25 | | -26=9+5x | | 7x(2)=63 | | (3/5)2 | | 0.25x=(9/365)x | | x^4-12x^3+36x^2-20x+3=0 | | x+(x*.12)=765 | | I-(1+7x)-6(-7-x)=36 | | 15/20=3/x | | 8.3w-w-8.9=1.5 | | -6x-6=10 | | 19/21-2/3 | | 6y+9=2thirdsx | | -6x+3=10 | | X^2-45x+506=0 | | (-2/7)^3 | | [9(n+5)-19]-[3(n-4)+2]= | | -6x-3=10 | | -100a^2-9=0 | | 3x^2-5x+20=0 | | X^2-42x+440=0 | | -8(r-1)=-24 | | .5(8x-8)=4x+6 | | 3+35x=175 | | 4*(4/7)^2*(-3/4)^3 | | 12x+4=10x+1 | | 5x2-x4/10 |

Equations solver categories